Optimal Coordination of Directional Overcurrent Protection Relays Using Genetic Algorithm - Ngo, Minh Khoa; Huynh, Van Trong; Vo, Hoang Long; Pham, Thi Nha Han (Journal of Technical Education Science, 2024)
This paper studies on establishing the mathematical optimization formulation to coordinate the operating times of directional overcurrent relays in transmission networks. The objective function of this optimization formulation is to minimize the total operation time of all directional overcurrent relays, and it must satisfy the highly nonlinear constraints such as the time multiplier setting range, the plug setting range, and the coordination time interval between the primary and backup relay pair. The optimal variables consist of the time multiplier setting and the plug setting which are determined by applying the genetic algorithm on MATLAB software. This optimization formulation is evaluated and validated via the simulation results of the test systems including the 4-bus network and 9-bus network. These test systems are modeled and simulated by using PowerWorld software to calculate the power flow results in the steady state and the short-circuit currents flowing the primary/backup relay pair. The simulation results confirm that the operating time coordination of directional overcurrent relays is capable of meeting the requirements of a relay protection system, improving the reliability of power system.